Historical Value Matrix of the Relics of the Sriwijaya Musi River Objects as Source Local History Learning in Palembang - Sholeh, Kabib; ., Warto; ., Djono (KnE Social Sciences, 2024)
Historical relics of the Musi River during the Sriwijaya period in Palembang are of various types and forms. Understanding their historical values is crucial for history learning Ironically, many members of the public do not comprehend the historical value embedded in these objects. Therefore, it is necessary to compile a data matrix of historical objects and and analyze their value This process can serve as a source for learning local history in Palembang. The purpose of this research is to analyze and construct a matrix of values for the historical legacy objects from the Musi River during the Srivijaya period. This matrix serves as a source for learning local history in Palembang The research employed a descriptive qualitative method, employing data collection techniques that include observation, documentation, in-depth interviews, and library study. Data analysis employed a narrative descriptive analysis. This study produced an organized matrix of relics from the Musi River during the Sriwijaya era, including ceramics, beads, statues, and porcelain. These historical artifacts bear marks past life in political, economic, socio-cultural and religious fields. The historical values of objects from the Musi River during the Sriwijaya era is highly relevant to the study of Indonesian History during the Hindu-Buddhist period. It can be concluded that these historical marks can serve as source learning history local in Palembang